Designing a Heart Rate and Body Temperature Measurement Tool Using Pulse Sensor and IR MLX90614 Based on ATmega328 and GSM Technology - Hatimah, Husnul; Gunawan, A. A. Ngurah; Alit Paramarta, Ida Bagus (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
The measurement of heart rate and body temperature are two of the five Vital Signs that indicate human health. During this time the heart rate is measured using a stethoscope or counting the heart rate through the wrist but this can cause a Human Error. So a tool is designed that can measure heart rate and body temperature using pulse sensor and IR MLX90614 besed on ATmega328 which results can be displayed through the website with patients having their own ID so that the data is not mixed with other patient data and equipped with a database so that it can store patient data. From the results of trials on 3 subjects classified according to the age of 5, 9 and 23 years. The average accuracy of heart rate and body temperature measurements between the design tools and standard equipment is 98.54% for heart rate and 95.97% for body temperature.